Analisis Pengaruh Radiasi Gelombang Elektromagnetik Terhadap Kesehatan - Nurfadhilah eka putri; Yushardi; Sudarti (CV. ITTC INDONESIA, 2023)
Electromagnetic radiation exposure impacts human health, including radiation sources such as X-rays, gamma rays, and electronic devices, particularly cellular phones. Exposure to electromagnetic radiation can cause a variety of health impacts, including central nervous system syndrome, nausea, headaches, insomnia, and even an increased risk of cancer. The physiological and psychological effects of electromagnetic radiation are also discussed in detail, with a focus on hypersensitivity and electrosensitivity, which can cause symptoms such as headaches, fatigue and insomnia. The article also discusses the impact of electromagnetic radiation from mobile phones and discusses the specific absorption rate (SAR) and the measurement limits set. This study highlights the need for further research to provide a more comprehensive understanding of the impact of electromagnetic radiation on human health.